Biological Potential, Gastrointestinal Digestion, Absorption, and Bioavailability of Algae-Derived Compounds with Neuroprotective Activity: A Comprehensive Review - Martins, Bruna (2022)
Currently, there is no known cure for neurodegenerative disease. However, the available therapies aim to manage some of the symptoms of the disease. Human neurodegenerative diseases are a heterogeneous group of illnesses characterized by progressive loss of neuronal cells and nervous system dysfunction related to several mechanisms such as protein aggregation, neuroinflammation, oxidative stress, and neurotransmission dysfunction. Neuroprotective compounds are essential in the prevention and management of neurodegenerative diseases. This review will focus on the neurodegeneration mechanisms and the compounds (proteins, polyunsaturated fatty acids (PUFAs), polysaccharides, carotenoids, phycobiliproteins, phenolic compounds, among others) present in seaweeds that have shown in vivo and in vitro neuroprotective activity. Additionally, it will cover the recent findings on the neuroprotective effects of bioactive compounds from macroalgae, with a focus on their biological potential and possible mechanism of action, including microbiota modulation. Furthermore, gastrointestinal digestion, absorption, and bioavailability will be discussed. Moreover, the clinical trials using seaweed-based drugs or extracts to treat neurodegenerative disorders will be presented, showing the real potential and limitations that a specific metabolite or extract may have as a new therapeutic agent considering the recent approval of a seaweed-based drug to treat Alzheimer’s disease